Humoral immune responses to HIV in the mucosal secretions and sera of HIV-infected women - Mestecky, Jiri; Wei, Qing; Alexander, Rashada; Raska, Milan; Novak, Jan; Moldoveanu, Zina (American journal of reproductive immunology (New York, N.Y., 2014)
Although sera and all external secretions contain antibodies to human immunodeficiency virus (HIV), their levels, specificity, isotypes, and relevant effector functions display a great degree of variability. Antibodies that bind HIV antigens and neutralize the virus are predominantly associated with the IgG isotype in sera and in all external secretions, even where total levels of IgG are much lower than those of IgA. Rectal fluid that contains high IgA, but low IgG levels, displayed low neutralizing activity independent of antibodies. Therefore, external secretions should be evaluated before and after selective depletion of Ig. At the systemic level, HIV-specific IgA may interfere with the effector functions of IgG, as suggested by recent studies of individuals systemically immunized with an experimental HIV vaccine. Although HIV-specific IgG and IgA antibodies may exhibit their protective activities at mucosal surfaces through interference with viral entry and local neutralization at the systemic level, such antibodies may display discordant effector functions.
Keywords: HIV Antibodies; Humans; Antibodies, Neutralizing; imunoglobulin G; HIV infekce; Mucous Membrane; HIV protilátky; HIV Infections; Vaginal Douching; Female; neutralizující protilátky; lidé; Immunoglobulin A; mucosal immunity; HIV antigeny; ženské pohlaví; Immunity, Humoral; secretory IgA and IgG; vaginální výplach; imunoglobulin A; sliznice; HIV Antigens; human immunodeficiency virus; Immunoglobulin G; Antibody responses; HIV-1; humorální imunita